A comparison of postoperative outcomes between robotic-assisted and laparoscopic-assisted total gastrectomy: a comprehensive meta-analysis and systematic review - Jianhua Chen; Fei Wang; Yong Wang; Jie Zhou; Yapeng Yang; Ziming Zhao; Rongfan Wu; Liuhua Wang; Jun Ren (BMC Surgery)
Abstract Background The application of robot-assisted technology in gastric cancer surgery is gradually gaining attention from surgeons. In this meta-analysis, our main objective was to assess whether robot-assisted techniques are more advantageous than laparoscopic-assisted technology in total gastrectomy. Methods We searched Pubmed, Embase, Web of Science, and Cochrane Library databases for clinical studies published before October 2023 comparing robotic-assisted total gastrectomy (RATG) and laparoscopic-assisted total gastrectomy (LATG) for gastric cancer. Non-clinical studies, data unavailability, or fewer than 50 included cases were excluded. The Newcastle-Ottawa Scale was used to assess the risk of bias by determining the quality of the observational studies. Statistical meta-analysis and drawing were performed using the Software Review Manager version 5.3 and Stata version 16.0. P < 0.05 was considered significant. Results Nine studies that included 1,864 patients with gastric cancer were included, published between 2012 and 2023. The results of the analysis showed that RATG has advantages in the following aspects: intraoperative blood loss was 17.69 ml lower in the RATG group than in the LATG group (WMD: -17.69,95% CI:-20.90 ∼ -14.49; P < 0.05); In terms of the number of resected lymph nodes, the RATG group had 2.65 more than the LATG group (WMD: 2.65,95% CI:0.88 ∼ -4.42); P < 0.05); the time to start liquid and postoperative hospital stays were 0.62 and 0.90 days shorter in the RATG group than in the LATG group, respectively (WMD: -0.62,95%CI: -1.06 ∼ -0.19; P < 0.05), (WMD: -0.90,95%CI: -1.43 ∼ -0.37; P < 0.05)); the incidence of major complications and pancreas fistula in the RATG group was 0.59% and 0.17% lower than in the LATG group, respectively (OR: 0.59,95% CI: 0.38 ∼ 0.93; P < 0.05), (OR: 0.17,95% CI: 0.03 ∼ 0.94; P < 0.05). However, the analysis showed that the operative time in the RATG group was 30.96 min longer than in the LATG group (WMD: 30.96,95% CI: 21.24 ∼ 40.69; P < 0.05). Conclusions Based on the results of this meta-analysis, we concluded that robotic-assisted technology may be a worthwhile technique to apply in the surgical treatment of total gastrectomy. However, this meta-analysis has the limitations that the included studies were all non-randomized controlled trials and published in Asian countries, and more high-quality randomized controlled trials are needed for further validation in the future. The registered name and registration number The study protocol for this meta-analysis is registered on the PROSPERO website under registration number CRD42024500512.